2019
DOI: 10.1113/ep087423
|View full text |Cite
|
Sign up to set email alerts
|

Foramen ovale blood flow and cardiac function after main pulmonary artery occlusion in fetal sheep

Abstract: New Findings What is the central question of this study?At near‐term gestation, foramen ovale blood flow accounts for a significant proportion of fetal left ventricular output. Can the foramen ovale increase its volume blood flow when right ventricular afterload is increased by main pulmonary artery occlusion? What is the main finding and its importance?Foramen ovale volume blood flow increased during main pulmonary artery occlusion. However, this increase was attributable to an increase in fetal heart rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In other words, a drop in the lung volume blood flow would lead to a decrease in the LVCO and an increase in the retrograde component in the aortic isthmus blood flow pattern. We have shown that foramen ovale has a limited capacity to increase its volume blood flow (18,29). These findings suggest that fetal pulmonary blood flow has an important role in the regulation of left ventricular output and hemodynamics in the aortic isthmus.…”
Section: Discussionmentioning
confidence: 73%
“…In other words, a drop in the lung volume blood flow would lead to a decrease in the LVCO and an increase in the retrograde component in the aortic isthmus blood flow pattern. We have shown that foramen ovale has a limited capacity to increase its volume blood flow (18,29). These findings suggest that fetal pulmonary blood flow has an important role in the regulation of left ventricular output and hemodynamics in the aortic isthmus.…”
Section: Discussionmentioning
confidence: 73%
“…In this way, we believe a new method for fetal foramen ovale haemodynamic evaluation may be created, instead of using animal models, to study the importance of FO [15].…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in left ventricular preload could then result in the reduced left ventricular cardiac output observed in this study with intra-amniotic Ureaplasma infection. The foramen ovale, which shunts oxygenated blood from the right atrium to the left atrium, bypassing the fetal pulmonary circulation, functions close to its maximum capacity 50,51 so cannot increase left atrial flow in order to compensate for this drop in pulmonary venous return. The finding of decreased mitral valve E/A ratio in the infected group (i.e.…”
Section: Fetal Hemodynamic Responses To Intra-uterine Infectionmentioning
confidence: 99%